Settlement of Land Disputes with The Title of Property Right Post Judges Decision (The Study of Land Disputes Bambu Runcing) - Handayani, Tuti; Asikin, Zainal; Dwi Putro, Widodo (International Journal of Scientific Research and Management (IJSRM), 2019)
This study aims to analyze state land dispute resolutions that are certified after the Judge's Decision (The Study of Land Disputes Bambu Runcing), Execution Process Implementation completion of post-Decision eta settlement: Submitting application for the execution of number: R/22/IX/2014/Bidkum on 23 sept 2014; Letter of request for rescheduling Execution No. R/30/XI/2014/Bidkum dated 27 November 2014; Minutes of Execution of Mataram District Court No:31/Pdt.G/2011/PN.MTR on Dec. 18. 2014; Calling to the dormitory dwellers in dispute to discuss the land emptying that has permanent legal force in the building of Sasanan Dharma Regional Police of NTB; Conducted the NTB Regional Police Chief Meeting with Members of the Indonesian National Police and Civil Servants who occupied the Bamboo Runcing Dormitory, 25 November 2014 attended by key officials, police chiefs, Mataram District court clerks, Mataram officials, Telkom Mataram officials, who were located Rupat Ops NTB Regional Police Chief; Giving compassion (to residents of full-fledged Indonesian police dormitories in disputes about “sharp bamboo land”; held by the Regional Police of West Nusa Tenggara: No. 3329 K/PDT/2012; No. 31/PDT.G/2011/PN.MTR; No. 48/PDT/2012/PT.MTR.